MUSIC, SPIRITUALITY, AND MENTAL HEALTH: A SYSTEMATIC REVIEW OF THE LITERATURE ON THE PSYCHOSOCIAL IMPACTS OF GOSPEL AND CONTEMPORARY RELIGIOUS MUSIC - Camila Souza Gonçalez, Jessika (Revista Gênero e Interdisciplinaridade, 2025)
Music of a spiritual and religious nature, especially gospel music, represents an important cultural phenomenon and a symbolic resource for millions of people. However, the scientific evidence on its impacts on mental health is dispersed. This systematic review, conducted under the PRISMA guidelines, seeks to consolidate the evidence on the relationship between religious/gospel music and outcomes in mental health, well-being, and resilience. The search was carried out in the PubMed, Scopus, Web of Science, PsycINFO, and SciELO databases. The results indicate a positive association between listening to and practicing religious music and the reduction of anxiety (including death anxiety), the increase in life satisfaction, self-esteem, and sense of control. Religious music acts as an effective coping strategy for managing stressful events, promoting feelings of comfort, strength, and peace, especially in African-American and elderly populations. The underlying mechanisms involve neurobiological (release of endorphins), psychosocial (community connection, reframing), and spiritual (connection with the transcendent) aspects. The evidence suggests that active engagement with music (singing, playing) enhances the effects on resilience. It is concluded that religious and gospel music is a valuable and culturally relevant resource for the promotion of mental health, with the potential to be integrated into non-clinical care interventions.Music of a spiritual and religious nature, especially gospel music, represents an important cultural phenomenon and a symbolic resource for millions of people. However, the scientific evidence on its impacts on mental health is dispersed. This systematic review, conducted under the PRISMA guidelines, seeks to consolidate the evidence on the relationship between religious/gospel music and outcomes in mental health, well-being, and resilience. The search was carried out in the PubMed, Scopus, Web of Science, PsycINFO, and SciELO databases. The results indicate a positive association between listening to and practicing religious music and the reduction of anxiety (including death anxiety), the increase in life satisfaction, self-esteem, and sense of control. Religious music acts as an effective coping strategy for managing stressful events, promoting feelings of comfort, strength, and peace, especially in African-American and elderly populations. The underlying mechanisms involve neurobiological (release of endorphins), psychosocial (community connection, reframing), and spiritual (connection with the transcendent) aspects. The evidence suggests that active engagement with music (singing, playing) enhances the effects on resilience. It is concluded that religious and gospel music is a valuable and culturally relevant resource for the promotion of mental health, with the potential to be integrated into non-clinical care interventions.